1959
DOI: 10.1111/j.1471-4159.1959.tb13211.x
|View full text |Cite
|
Sign up to set email alerts
|

The Urinary Excretion of Adrenaline and Noradrenaline by Schizophrenic Patients During Reserpine Treatment

Abstract: IN animal experiments several investigators have demonstrated the depletoxy action of reserpine on the stores of catecholamines (CARLSON and HILLARP, 1956; BERTLER, CARLSSON and ROSENGREN, 1956; HOLZBAUER and VOCT, 1956; BRODIE, OLIN, K u " and SHORE, 1957; CARLSSON, ROSENGREN, BERTLER and NILSON, 1957; STJ-and SCHAPIRO, 1958). In patients treated with reserpine BURGER (1957) found a decrease in blood noradrenaline, and GADDUM et al. (1958) reported a diminished excretion in urine of adrenaline and noradrenali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

1963
1963
1973
1973

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Several-times repeated injections of heat-killed cells, toxic endotoxins, or CH30K detoxified derivative thereof (endotoxid-2) result in a comparable antibody titer after [8][9][10] injections. Several-times repeated injections of heat-killed cells, toxic endotoxins, or CH30K detoxified derivative thereof (endotoxid-2) result in a comparable antibody titer after [8][9][10] injections.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several-times repeated injections of heat-killed cells, toxic endotoxins, or CH30K detoxified derivative thereof (endotoxid-2) result in a comparable antibody titer after [8][9][10] injections. Several-times repeated injections of heat-killed cells, toxic endotoxins, or CH30K detoxified derivative thereof (endotoxid-2) result in a comparable antibody titer after [8][9][10] injections.…”
mentioning
confidence: 99%
“…Several-times repeated injections of heat-killed cells, toxic endotoxins, or CH30K detoxified derivative thereof (endotoxid-2) result in a comparable antibody titer after [8][9][10] injections. Chronic administration of reserpine in man is associated with decreased VMA excretion (8), decreased urinary excretion of norepinephrine (NE) (7,9), and decreased ( 7 ) or unchanged (9) excretion of epinephrine Bmause both increased and decreased cateoholamine and VMA excretion have been reported follouring reserpine administration the present study has been designed to determine the effect of acute and repeated administration of reserpine on the pattern of VMA excretion in man. While toxic preparations produce both 2-Me resistant and sensitive antibodies from the beginning of the immunization, enddoxoid-2 produces almost exclusively 2-Me sensitive antibodies in the first 10 days.…”
mentioning
confidence: 99%
“…Other studies in adults have attempted to correlate clinical responses with the urinary excretion of certain catechols and indoles,t' 11,17,29 because in the brain of the laboratory animal, norepinephrine, dopamine, and serotonin are depleted following reserpine administration which is accompanied with sedation. 41 However, reports from studies in humans have been at variance.…”
mentioning
confidence: 99%
“…41 However, reports from studies in humans have been at variance. l , 11,17,29 This may be due, in part, to the well-recognized difficulty in controlling the diet and environment of patients. 23 , 25, 28, 34 By detennining the parent catecholamines and their major metabolites in urine of patients (children) whose diet, activity, and environment could be controlled, in addition to making certain physiologic measurements, this study attempts to relate more definitively the biochemical and clinical effects produced by reserpine.…”
mentioning
confidence: 99%
“…Several aspects of the alterations in body function associated with administration of reserpine to man have been reported: in two schizophrenics who had received reserpine, de la Lande and associates (6) showed that ephedrine infused into the brachial artery had no effect on forearm blood flow; Westfall and Watts (7) showed that in normal students there was a diminished response of blood pressure and finger temperature to smoking after fourteen days of reserpine administration; Burger (8) found diminished plasma norepinephrine levels, and Gaddum, Krivoy, and Laverty (9) and Carlsson, Rasmussen, and Kristjansen (10) described decreased urinary excretion of catecholamines after long term reserpine administration. However, there appear to be no formal studies in man showing that reserpine affects cardiovascular responses, as has been postulated to explain the circulatory collapse which may occur in patients who have received reserpine and are subjected to anesthesia ( 11 ) and shock therapy (12).…”
mentioning
confidence: 99%